Calcium Acetate Versus Calcium Carbonate as Oral Phosphate Binder: Preparation and In Vitro Assessment: Calcium acetate as oral phosphate binder - Tavakoli, Naser; Jafarian, Abbas; Najmi, Farzin (Iranian Journal of Pharmaceutical Sciences, 2005)
Calcium acetate is used as an oral phosphate binder to control hyperphosphatemia in patients with chronic renal failure. Compared to calcium carbonate, control of hyperphosphatemia can be achieved at lower calcium administration with calcium acetate which likely reduces the risk of hypercalcemia. In this study, various formulations of calcium acetate tablets were prepared and their disintegration times, dissolution rates and phosphate binding capacities were determined. Dissolution test was carried out using the paddle method according to the United States Pharmacopoeia (USP XXIII). The binding efficiency of the tablets was compared by measuring the amount of insoluble phosphate after mixing with a sodium phosphate solution at pH 6. Calcium acetate tablets had a mean content of 809.6 mg of calcium acetate and a mean weight of 1087 mg. The average breaking load and disintegration times were 66.4±5.5 N and 24.5±2.1 min, respectively. Drug release after 30 and 60 min were 80.45% and 101.42%, respectively. The amount of nondissolved phosphorus following 60 min incubation of calcium acetate and/or calcium carbonate tablets were 372.8 mg (61.2%) and 463.2 mg (76.0%), respectively. Weight variation, friability, disintegration time, and dissolution rate of calcium acetate tablets were in the acceptable pharmacopoeial limits. Ahigh phosphate binding capacity of calcium acetate tablets indicated that it can be a suitable alternative to calcium carbonate in the management of hyperphosphatemia in patients with chronic renal failure.